Evaluation of a Major Surface Antigen of Babesia microti Merozoites as a Vaccine Candidate against Babesia Infection - Man, Suqin; Fu, Yongfeng; Guan, Yue; Feng, Meng; Qiao, Ke; Li, Xueping; Gao, Hongjian; Cheng, Xunjia (Frontiers in Microbiology, 2017)
Babesia species are tick-borne intraerythrocytic protozoa that cause babesiosis in humans worldwide. No vaccine has yet proven effective against Babesia infection. Surface antigens of merozoites are involved in the invasion of erythrocytes by Babesia. Surface antigens may be presented by both babesial sporozoites and merozoites and provide a general target for antibody-mediated inhibition of erythrocyte invasion. Here we evaluated a major surface antigen of B. microti merozoites, BMSA, as a potential vaccine to prevent babesiosis. Our data indicated that bmsa is transcribed during different phases, including ring form, amoeboid form, and merozoites, and that its expression is significantly increased in mature merozoites. The protein was found to be located in the membrane of B. microti and in the cytoplasm of infected erythrocytes. The immune response induced by BMSA had a significant inhibitory effect on parasite invasion of the host erythrocytes (83.3% inhibition of invasion) and parasite growth in vivo. The levels of parasitemia significantly decreased after BMSA vaccination when mice were infected with babesia parasite. Importantly, protective immunity was significantly related to the upregulation of the Th17 cytokine interleukin-17, the Th1 cytokine interleukin-12p70 and the Th2 cytokines, such as interleukin-4, -6, and -10. Ingenuity Pathway Analysis indicated that interleukin-17 facilitated the secretion of Th2 cytokines, such as interleukin-10, -4, and -6, thereby inducing a predominately Th2 protective immune response and promoting the expression a high level of special IgG1 against Babesia infection. Further, an anti-BMSA monoclonal antibody successfully protected NOD/SCID mice from a challenge with B. microti. Taken together, our results indicated that BMSA induces a protective immune response against Babesia infection and may serve as a potential vaccine.